2005
DOI: 10.4315/0362-028x-68.12.2510
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Salmonella, Escherichia coli O157:H7, and Other Bacterial Populations in Commercial and Laboratory-Scale Sprouting Mung Bean Beds

Abstract: The reliability of testing spent irrigation water to assess the microbiological status of sprouting mung bean beds has been investigated. In commercial trials, the distribution of opportunistic contaminants within 32 bean sprout beds (25 kg of mung beans per bin) was assessed 48 h after germination. The prevalence of generic Escherichia coli, thermotolerant coliforms, and Aeromonas in sprouts (n = 288) was 5, 11, and 39%, respectively, and 57, 70, and 79% in the corresponding spent irrigation water samples (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…In laboratory experiments with artificial inoculation of seeds (Charkowski et al, 2002;Liu and Schaffner, 2007b), and with naturally contaminated seeds (Stewart et al, 2001), the number of pathogens in the sprouting water was similar to that on the sprouts, after some times of sprouting. In contrast, (Hora et al, 2005) showed that Salmonella artificially inoculated in a few seeds placed in the seedbed before sprouting did not always result in Salmonella being found in the water irrigating the seeds. In addition, inoculation of seeds during the sprouting process with Salmonella or L. monocytogenes, instead of inoculation at the start of sprouting, resulted in no multiplication of these pathogenic bacteria (Castro-Rosas and Escartin, 2000;Schoeller et al, 2002).…”
Section: Sprouted Seedsmentioning
confidence: 87%
See 2 more Smart Citations
“…In laboratory experiments with artificial inoculation of seeds (Charkowski et al, 2002;Liu and Schaffner, 2007b), and with naturally contaminated seeds (Stewart et al, 2001), the number of pathogens in the sprouting water was similar to that on the sprouts, after some times of sprouting. In contrast, (Hora et al, 2005) showed that Salmonella artificially inoculated in a few seeds placed in the seedbed before sprouting did not always result in Salmonella being found in the water irrigating the seeds. In addition, inoculation of seeds during the sprouting process with Salmonella or L. monocytogenes, instead of inoculation at the start of sprouting, resulted in no multiplication of these pathogenic bacteria (Castro-Rosas and Escartin, 2000;Schoeller et al, 2002).…”
Section: Sprouted Seedsmentioning
confidence: 87%
“…Evidence for heterogenous distributions of bacterial pathogens have been observed for: seeds (FDA, 1999c;ISS, 2011;Van Beneden et al, 1999); irrigation water (Liu and Schaffner, 2007a;McEgan et al, 2008); sprouts and spent irrigation water (Hora et al, 2005;Liu and Schaffner, 2007a;McEgan et al, 2008).…”
Section: Heterogenous Distribution Of Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Inactivation of potential biological contaminants without altering the freshness of the product is impractical, and therefore water of a high microbiological quality is essential for the production of safe fresh food (22). Unfortunately, considerable evidence indicates the involvement of contaminated water in the production of berries, sprouts, and green-leafed vegetables (2,12,19,26). Microsporidian spores resist standard wastewater treatment and can be found in sewage sludge end products commonly used for fertilization of ready-to-eat crops or in runoff-impacted surface water used for irrigation (15).…”
mentioning
confidence: 99%
“…Microsporidian spores have been reported to be found in samples from groundwater and surface water (3, 4, 7-10, 13, 24), including water used for irrigation of fresh-produce operations (26). Although berries, sprouts, and vegetables have been contaminated with a variety of human pathogens (12,17,19,21,22,25), reports on contamination with microsporidian spores are scant (1). Because E. intestinalis has been identified in irrigation water used for ready-to-eat crop production (26) and since unspecified spore species have been found in samples from strawberries, lettuce, and parsley (1), we initiated testing of commercial fresh produce at the retail level to quantitatively assess contamination with human-virulent microsporidian spores.…”
mentioning
confidence: 99%